2021
DOI: 10.1111/jcmm.16807
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin up‐regulates the decrease of myocardial autophagic flux induced by β1‐adrenergic receptor autoantibody partly dependent on AMPK

Abstract: Cardiomyocytes autophagy is essential for maintaining cardiac function. Our previous studies have found that β1‐adrenergic receptor autoantibody (β1‐AA) induced the decreased myocardial autophagic flux, which resulted in cardiomyocyte death and cardiac dysfunction. And other studies demonstrated that β1‐AA induced the decrease of AMPK phosphorylation, the key hub of autophagy pathway, while adiponectin up‐regulated autophagic flux mediated by AMPK. However, it is not clear whether adiponectin improves the inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…The mechanisms behind these effects remain to be fully defined. We and others have now demonstrated that adiponectin stimulates autophagy flux in cardiomyocytes 21,32,33 . The link between autophagy and cell death in models of MI has been previously established 4,34 and the majority of studies indicate that induction of autophagy is a protective mechanism that reduces the extent of ischemia‐induced acute cell damage and also reduces the extent of postinfarction cardiac remodeling and dysfunction 6,35 .…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…The mechanisms behind these effects remain to be fully defined. We and others have now demonstrated that adiponectin stimulates autophagy flux in cardiomyocytes 21,32,33 . The link between autophagy and cell death in models of MI has been previously established 4,34 and the majority of studies indicate that induction of autophagy is a protective mechanism that reduces the extent of ischemia‐induced acute cell damage and also reduces the extent of postinfarction cardiac remodeling and dysfunction 6,35 .…”
Section: Discussionmentioning
confidence: 87%
“…Other studies have also indicated that adiponectin can directly stimulate myocardial autophagy and consequently confer cardioprotection. 21,32,33 Using echocardiography, including strain analysis, we observed that mice lacking adiponectin had an enhanced degree of cardiac dysfunction. Correlated with this was a significant increase in indices of cell death, such as more TUNEL positive cells and increased Bcl2:BAX ratio in Ad-KO versus WT mice after ischemia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…AdipoRon treatment promotes autophagy and improves renal fibrosis in salt-hypertensive mice by activating the AMPK/ULK1 pathway ( Li et al, 2021 ). Notably, in cardiomyocytes pretreated with compound C, the adiponectin treatment did not improve the decreased autophagosome formation but improved the decreased autophagosome clearance induced by β1-adrenergic receptor autoantibody ( Sun et al, 2021 ). Exercise leads to AMPK activation in the muscle in normal mice but not in autophagy-defective mice ( Garber, 2012 ).…”
Section: Adiponectin and Osteoarthritismentioning
confidence: 99%